THE EFFECT OF INFLUENCE OF EXPERIENCE AND AGE OF THE ARTIFICIAL INSEMI- NATION OFFICER ON THE SUCCESS OF ARTIFICIAL INSEMINATION IN DAIRY COWS - A., SUDRAJAT; ASRAF, R. J.; UTOMO, S.; CHRISTI, R. F. (Majalah Ilmiah Peternakan; Vol 26 No 2 (2023): Vol. 26 No. 2 (2023), 2024)
Research on the effect of influence of experience and age of the artificial insemination officer on the success of artificial insemination (AI) in dairy cows has been conducted. This study aims to determine and examine the ef- fect of influence of experience and age of the artificial insemination officer on the success of artificial insemination (AI) in dairy cows. The research was conducted in December 2022–January 2023 in Lembang District, Bandung Barat. The method used is the survey method. The material used was an artificial insemination officer at the Kope- rasi Peternak Sapi Bandung Utara (KPSBU) Lembang. The variables observed to determine AI success are service conception (S/C), conception rate (C/R). The data analysis used in this study is quantitative descriptive analysis and simple correlation analysis. The results showed that the AI officer experience was an average of 19 years and an average age of 39 years. Average S/C value is 1.84 , Average C/R value is 64.50%. The results of a simple correlation analysis showed that the experience and age of the inseminator had no real effect (P>0.05) on the success of AI in dairy cows. It was concluded that the success rate of AI in dairy cattle based on S/C and CR in Lembang District was good, but the experience and age of the artificial insemination officer did not have a significant effect on the success of artificial insemination in dairy cows.